Pengadaan Papan Informasi dan Kotak Saran di Desa Idalolong, Kecamatan Nagawutung - Aprilia Trivonita Wagur; Theresia W Gordon; Maria Julianti Gego; Jecky Mirando Nenohai; Emanuel Kosat; Marianus Kleden (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Information boards and suggestion boxes are important things that village governments need to provide assistance to the community. Idalolong village is a part of Nagawutun sub-district which is located in Lembata Regency. The provision of this information board serves as a platform to make it easier for the public to find information related to public services and to increase transparency and accountability of the village government. This service activity involved local village officials and the Real Work Lecture (KKN) group 10 at Widya Mandira University, Kupang. This activity was carried out at the Idalolong Village Office, Nagawutun sub-district, Lembata Regency. By creating this information board and suggestion box, it will be easier for the community to find out information and the Village government can accommodate input, suggestions and complaints from the village community.